Empowering female teachers through digital competence and AI integration to improve teaching effectiveness in Islamic Schools in Southern Pakistan - Muhammad Kashif Majeed; Tunku Badariah Ahmad; Aizat Bin Shamsuddin (An-Nisa’ Journal of Gender Studies, 2025)
Female teachers in Islamic schools in Southern Punjab, Pakistan face unequal digital access, minimal Artificial Intelligence (AI) integration, and stark variations in digital competence. These conditions undermine teaching effectiveness and professional empowerment, with extreme regional disparities that cannot be ignored. This study analyzes regional differences in digital technology utilization, AI adoption, and informal digital learning, as well as how variations in access, digital competency, and institutional support influence teaching effectiveness among female teachers in Islamic secondary schools. Using a quantitative approach, the study examined the effects of digital competency, AI use, and informal digital learning on teaching effectiveness with 450 valid and reliable respondents, employing multiple regression analysis. The findings indicate that the empowerment of female teachers in Southern Pakistan varies across districts. First, female teachers’ contributions to instructional tasks differ regionally. Second, workload distribution and technology adoption also vary. Third, female teachers demonstrate strong digital competence and actively engage in informal learning; however, technology adoption is influenced by regional contexts. The study concludes that the empowerment of female teachers through digital competence and AI in Southern Pakistan is shaped by regional contexts. Variations in contributions across districts indicate a dependence on local ecosystems and adaptive capacity, rather than merely access to technology. This study contributes to highlighting the importance of institutional support, revealing structural inequalities, and emphasizing the role of informal learning over AI adoption in empowering female teachers.